SCIENTIFIC AND PEDAGOGICAL ACTIVITY OF PROFESSOR V.I. KROKOS, THE FIRST DEAN OF THE GEOLOGICAL AND GEOGRAPHIC FACULTY OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. THE 130-TH ANNIVERSARY OF THE BIRTHDAY - Shatalov, N. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article is devoted to the research of scientific and pedagogical activity of Vladimir Ivanovich Krokos (1889–1936). an outstanding Ukrainian geologist, geomorphologist, soil scientist, paleontologist, zoologist, stratigraphist, geologist, first dean of the geological-geographical faculty of Taras Shevchenko Kyiv National University. It also displays the main stages of the life and scientific and pedagogical work of the scientist in Odessa and Kyiv.
Keywords: V. Crocos; first dean; geologist; geomorphologist; soil scientist; paleontologist; zoologist; stratigraphist